Livedo reticularis in a patients with Wegener Granulomatosis. A case report. - Elly Moedijatmini Elly Moedijatmini (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
Livedo reticularis (LR) is a skin lesion which is characterized by a reddish blue mottling in a fishnet reticular pattern. Although many diseases have been considered as causative of LR, Wegener's Granulomatosis (WG) has never been reported to be associated with LR.A case of LR was reported in a 70-year-old woman suffering from WG. However, it is difficult to conclude whether LR is a part of WG or only a coincident case. The vasculitis features as shown by histopathological skin examination suggest that the skin lesion might be a part of WG syndrome.Key words : livedoreticularis - Wegener granulomatosis - saddle nose - skin biopsy - vasculitis granulomatosis